2021
DOI: 10.1021/acscatal.1c03899
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Semi-Pinacolases from the Epoxide Hydrolase Family during Efficient Assembly of a Fungal Polyketide

Abstract: The semipinacol rearrangement (SPR) is highly useful in the asymmetric synthesis of complex compounds. In biological systems, only a few semi-pinacolases belonging to a few families have been identified to catalyze the SPR on alkaloids. Here, based on the biosynthesis of a fungal mycotoxin asteltoxin (1), two semi-pinacolases AstD/MrvD were identified from the epoxide hydrolase family to catalyze type III SPR on the polyketide backbone. They were proposed to catalyze efficient regio-selective hydrolysis on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 43 publications
(85 reference statements)
0
30
0
Order By: Relevance
“…20,21 Asteltoxin ( 4) is produced from marine-derived and moldy rice Aspergillus spp, 22,23 and we also reported its production in M. anisopliae, 24 while citreoviridin ( 5) is produced by Penicillium and Aspergillus spp. 25,26 They are structurally characterized as pyrone−polyene-derived natural products with a dioxabicyclooctane (DBO) ring (1−4) or tetrahydrofuran (THF) ring ( 5) 24 (Scheme 1). Citreoviridin (5) has been formally affirmed as a mycotoxin in food contamination, 6,27 increase its cytotoxicity to mammalian cells.…”
Section: ■ Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…20,21 Asteltoxin ( 4) is produced from marine-derived and moldy rice Aspergillus spp, 22,23 and we also reported its production in M. anisopliae, 24 while citreoviridin ( 5) is produced by Penicillium and Aspergillus spp. 25,26 They are structurally characterized as pyrone−polyene-derived natural products with a dioxabicyclooctane (DBO) ring (1−4) or tetrahydrofuran (THF) ring ( 5) 24 (Scheme 1). Citreoviridin (5) has been formally affirmed as a mycotoxin in food contamination, 6,27 increase its cytotoxicity to mammalian cells.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Previous work has shown that Omethylation on the α-pyrone of the PKS products (6,11) is required for FMO-catalyzed epoxidation during the biosynthesis of these mycotoxins (Scheme 1). 24,26,29 However, recent work on the biosynthesis of polyene natural products aspernidgulenes from A. nidulans showed that methylation is dispensable for the subsequent epoxidation, 33 though the PKS product of aspernidgulenes has a 5,6-dihydro-α-pyrone and more C-methylations but has an identical polyene tail with 6 and 11. This distinct independence of O-methylation for epoxidation prompted us to re-investigate whether methylation on 6 and 11 is essential for subsequent epoxidation since MTs and FMOs recognize two distant site on the substrates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A; Table S6 ) may be involved in producing more complex products from 1 . Among these four genes products, OrfA is a homolog of epoxide hydrolases, which were normally found in the transformation of the epoxides to the diols on some fungal secondary metabolites, such as asteltoxin and aurovertin E [ [33] , [34] , [35] , [36] ]. OrfB is a short-chain dehydrogenase/reductase, which shows the highest similarity to L-allo-threonine dehydrogenase homologous that were found in catalyzing the oxidation of L-allo-threonine to L-2-amino-3-keto-butyrate [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two bifunctional semipinacolases (SPases), AstD/MrvD, from the epoxide hydrolase family have been discovered from the biosynthetic pathway of the fungal polyketide, asteltoxin 31 . 23 The SPases were shown to catalyse both regioselective hydrolysis of a bis-epoxide intermediate and 2,3-migration of the resulting epoxide alcohol. Bioinformatic analysis of the genome sequence from Aspergillus burnettii has allowed the identification of the biosynthetic gene cluster involved in the production of the polyene-decalin polyketide, burnettiene A 32 .…”
mentioning
confidence: 99%